Administrative and clinical denials by a large dental insurance provider - Geraldo Elias MIRANDA; Marta Cristina Portes SIQUEIRA; Ricardo Luiz Siqueira Magalhães FERREIRA; Fábio DELWING; Eduardo DARUGE JÚNIOR (Sociedade Brasileira de Pesquisa Odontológica, 2015)
The objective of this study was to assess the prevalence and the type of claim denials (administrative, clinical or both) made by a large dental insurance plan. This was a cross-sectional, observational study, which retrospectively collected data from the claims and denial reports of a dental insurance company. The sample consisted of the payment claims submitted by network dentists, based on their procedure reports, reviewed in the third trimester of 2012. The denials were classified and grouped into 'administrative', 'clinical' or 'both'. The data were tabulated and submitted to uni- and bivariate analyses. The confidence intervals were 95% and the level of significance was set at 5%. The overall frequency of denials was 8.2% of the total number of procedures performed. The frequency of administrative denials was 72.88%, whereas that of technical denials was 25.95% and that of both, 1.17% (p < 0.05). It was concluded that the overall prevalence of denials in the studied sample was low. Administrative denials were the most prevalent. This type of denial could be reduced if all dental insurance providers had unified clinical and administrative protocols, and if dentists submitted all of the required documentation in accordance with these protocols.